2023
DOI: 10.1111/opo.13116
|View full text |Cite
|
Sign up to set email alerts
|

The association between time spent on screens and reading with myopia, premyopia and ocular biometric and anthropometric measures in 6‐ to 7‐year‐old schoolchildren in Ireland

Abstract: More time spent on near tasks has consistently been associated with the promotion of myopia. The World Health Organization advises limiting daily screentime to less than 2 h for children aged five and over. This study explored the relationship between time spent on screens and reading/writing with refractive status, ocular biometric and anthropometric factors in 6-to 7-year-olds in Ireland. Methods: Participants were 723 schoolchildren (377 boys [51.8%]), mean age 7.08 (0.45) years. The examination included cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 69 publications
0
12
1
Order By: Relevance
“…Therefore, it is important to consider the timing of data collection when comparing results from different studies. Although our results show that Spanish children after lockdown changed their habits by increasing time outdoors and decreasing the time for near vision activities and the use of electronic devices, some studies have reported an increased screen time and a decreased outdoor time among children during periods of strict COVID-19 regulations in other regions of the world ( 30–32 ). A recent systematic review ( 14 ) of the effects of remote learning during the COVID-19 lockdown on children’s visual health showed that most of the studies revealed a decline in visual health among children who were exposed to virtual learning strategies during the COVID-19 lockdown.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Therefore, it is important to consider the timing of data collection when comparing results from different studies. Although our results show that Spanish children after lockdown changed their habits by increasing time outdoors and decreasing the time for near vision activities and the use of electronic devices, some studies have reported an increased screen time and a decreased outdoor time among children during periods of strict COVID-19 regulations in other regions of the world ( 30–32 ). A recent systematic review ( 14 ) of the effects of remote learning during the COVID-19 lockdown on children’s visual health showed that most of the studies revealed a decline in visual health among children who were exposed to virtual learning strategies during the COVID-19 lockdown.…”
Section: Discussioncontrasting
confidence: 61%
“…Our results show that after the COVID lockdown, more than 50% of the children spent between 1.6 and 2.7 h per day outdoors. According to the latest meta-analysis, spending more time outdoors can slow down the change of axial length and decrease the risk of myopia (27); for each additional hour spent outdoors per week, the risk of developing myopia decreased by 2% (28) and the risk ratio for high versus low outdoor time was 0.54 to 0.57 in clinical trials and longitudinal cohort studies (29). In this sense, it would be convenient to explain to the families of children who are pre-myopic that they spend more time outdoors as a protection factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, screen time has eclipsed reading/writing time for Irish 6-to 7-year-olds. 7 The National Sleep Foundation reported virtually all Americans have a screen in their bedroom and use it within an hour of bedtime. 8 Global sleep patterns indicate that average sleep duration is decreasing.…”
mentioning
confidence: 99%
“…The ubiquitous adoption of handheld digital devices and screen media following the 2007 launch of the Apple iPhone (http://apple.com) has increased our exposure to blue‐rich white light from screens and digital devices in the evening and at night, disrupting our body's natural sleep cycle. For example, screen time has eclipsed reading/writing time for Irish 6‐ to 7‐year‐olds 7 . The National Sleep Foundation reported virtually all Americans have a screen in their bedroom and use it within an hour of bedtime 8 .…”
mentioning
confidence: 99%